Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1515/jpem-2019-0409
|View full text |Cite
|
Sign up to set email alerts
|

Is there a relationship between the dietary inflammatory index and metabolic syndrome among adolescents?

Abstract: BackgroundDietary patterns have a crucial role in modulating chronic inflammation. This study aimed to determine the relationship between the Dietary Inflammatory Index (DII) and inflammation markers and metabolic syndrome components in adolescents (n = 343).MethodsFasting glucose, fasting insulin and lipid profile were analyzed and blood pressures were measured. Analysis of inflammation markers such as sedimentation, leukocyte, C-reactive protein (CRP), tumor necrosis factor-alpha (TNF-α) and interleukin-6 (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 37 publications
1
14
1
Order By: Relevance
“…However, studies exploring the relation between dietary inflammatory potential and cardiometabolic risk factors among adolescents are scarce (15,16) . Most of the data for this age group show an association between the DII and inflammatory markers, like tumor necrosis factor (TNFα), interleukins (IL-1 and 2), interferon-gamma (INF-γ), and C-reactive protein, although levels of markers are divergent among studies (16)(17)(18) . Furthermore, there are few data linking DII scores and metabolic markers in adolescents, with inconsistent results (18,19) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies exploring the relation between dietary inflammatory potential and cardiometabolic risk factors among adolescents are scarce (15,16) . Most of the data for this age group show an association between the DII and inflammatory markers, like tumor necrosis factor (TNFα), interleukins (IL-1 and 2), interferon-gamma (INF-γ), and C-reactive protein, although levels of markers are divergent among studies (16)(17)(18) . Furthermore, there are few data linking DII scores and metabolic markers in adolescents, with inconsistent results (18,19) .…”
Section: Introductionmentioning
confidence: 99%
“…Most of the data for this age group show an association between the DII and inflammatory markers, like tumor necrosis factor (TNFα), interleukins (IL-1 and 2), interferon-gamma (INF-γ), and C-reactive protein, although levels of markers are divergent among studies (16)(17)(18) . Furthermore, there are few data linking DII scores and metabolic markers in adolescents, with inconsistent results (18,19) . Thus, we aimed to investigate the association between dietary inflammatory potential, assessed by the DII, and cardiometabolic risk factors in a large sample of Brazilian adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…The DII, a tool that assesses the inflammatory potential of a diet [32], was examined in 6 observational studies [38,51,[55][56][57][58], one of which was also discussed in Section 3.1.3 [51]. These studies found that adherence to a pro-inflammatory diet (indicated by a higher score in the DII) was associated with higher levels of hs-CRP, IL-6 and TNF-α in healthy males and females.…”
Section: Dietary Inflammatory Index (Dii)mentioning
confidence: 99%
“…The remaining two observational studies found an association between WDP adherence, and higher levels of CRP and IL-6 in this case in female cohorts of healthy participants ( Del Mar Bibiloni et al., 2013 ; Khayyatzadeh et al., 2018 ). Similarly, across the six observational studies ( Lazarou et al., 2010 ; Sen et al., 2018 ; Almeida-de-Souza et al., 2018 ; Coheley et al., 2019 ; Seremet Kurklu et al., 2020 ; Shivappa et al., 2017 ) that examined the Dietary Inflammatory Index (DII), a tool that assesses the inflammatory potential of a diet ( Suhett et al., 2020 ), diets with high inflammatory potential (a higher score in the DII), inducing a higher inflammatory response were positively associated with pro-inflammatory biomarkers in males and females. Specifically, higher levels of hs-CRP, IL-6 and TNF-α in healthy males and females.…”
Section: Dietary Intake and Inflammationmentioning
confidence: 99%
“…Specifically, higher levels of hs-CRP, IL-6 and TNF-α in healthy males and females. Four of the studies found a positive association between adherence to a pro-inflammatory diet (indicated by a higher score in the DII) and IL-6 ( Almeida-de-Souza et al., 2018 ; Seremet Kurklu et al., 2020 ), IL-1, IL-2, interferon gammon and sVCAM-1 in healthy males and females ( Shivappa et al., 2017 ), but also a positive association between DII and CRP in males and females with obesity ( Lazarou et al., 2010 ). However, two studies did not find any associations between the DII and CRP ( Sen et al., 2018 ), or IL-6, MCP-1 or TNF-α ( Coheley et al., 2019 ) in neither healthy males or females.…”
Section: Dietary Intake and Inflammationmentioning
confidence: 99%